Initial research of application of astaxanthin rich Haematococcus pluvialis biomass as supplenent dietary for salmon fish in Vietnam - Tam, Luu Thi; Thom, Le Thi; Ha, Nguyen Cam; Thu, Le Ha; Hong, Dang Diem (Academia Journal of Biology, 2015)
This study examined the effects of feed containing astaxanthin from Haematococcus pluvialis biomass on growth and flesh pigmentation in salmon in Vietnam. The salmon fish with an initial weight of 0.7 kg were used in this experiment. The fish were fed with three different feeds: imported bran (from France),  domestic bran (bran produced in Vietnam) and domestic bran added with astaxanthin from Haematococcus pluvialis alga biomass) in an experiment lasting for 55 days. Obtained results have shown that feed was supplemented with H. pluvialis biomass (with astaxanthin concentration approximate 61 mg.kg-1 feed) was no significant effect on the growth and flesh pigmentation of salmon. Growth of fish fed with feed supplemented H. pluvialis was lower in which growth parameters such as weight, length and width only values were about 64.77, 90.21 and 86.20 percent than that for salmon fed by the imported bran, respectively. However, the flesh quality of salmon was improved, particularly, canxi and DHA contents (docosahexaenoic acid - DHA; C22:6 n-3) of the flesh was significantly higher (p<0.05) in salmon fed the feed supplemented with H. pluvialis compared to salmon fed the unsupplemented feed. The calcium content of salmon flesh in experimental group was higher 2.09 and 4.26 times; DHA content was higher 1.69 and 1.2 times than that in salmon fed by the imported bran and the domestic bran, respectively. Obtained results in this report have shown that astaxanthin from H. pluvialis alga was supplemented into feed can improve the quality of salmon flesh.Author for correspondence: ddhong60vn@yahoo.com